UJI AKTIVITAS EKSTRAK ETANOL GAMBIR (Uncaria gambir Roxb.) TERHADAP PENYEMBUHAN LUKA BAKAR PADA KULIT PUNGGUNG MENCIT PUTIH JANTAN (Mus musculus) - Fitri Handayani; Eka Siswanto; Lintang Ayu Trisna Pangesti (Jurnal Ilmiah Manuntung, 2015)
Gambir (Uncaria gambir Roxb.) contains flavonoids, tannins, saponins and alkaloids that can help in the healing process of burns on the back skin of mice. Gambir has been used for the treatment because it has the effect of antimicrobial and anti-inflammatory. Gambir is used by the people as a traditional medicine to treat burns.This research is experimental research. The object studied is the potential of gambir extract on healing burns of mice back skin. The number of mice used are 15 which divided into 5 groups: the positive control group (branded ointment), negative control group (vaseline flavum), group of gambir ethanol extract and vaseline flavum concentration of 25%, 35%, and 45%. Each group consisted of 3 mice.Backs of the mice induced using a heated solder which tip contained stainlees plate measuring 1x1 cm and placed for 2 seconds on the back skin of mice. The percentage of burns healing is obtained by calculating the surface area of the wound. The data were analyzed using ANOVA analysis followed by LSD test. The results showed that ethanol extract of gambir concentration of 25% with the healing burns percentage of (72.00%), the concentration of 35% (85.00%), and the concentration of 45% (88.67%) have activity on healing burns of back skin of mice. The results of data analysis using ANOVA showed that the data has significant differences with a significance value <0.05 is 0.000. LSD test results stated that each treatment group have significant differences with a significance value <0.05. It can be seen that with increasing dose will be followed by duration of burns healing